ER stress and structural changes induced by rare WFS1 variant identified in autosomal dominant form of WFS1-related disorder - Silvia Borecka; Alexandra Zahradnikova; Lukas Varga; Juraj Stanik; Dominika Hromnikova; Miroslav Sabo; Marek Sklenar; Iuliia Baglaeva; Bogdan Iaparov; Michal Cagalinec; Martina Skopkova; Daniela Gasperikova (Molecular Medicine, 2026)
Abstract Background WFS1‑related disorders encompass a broad phenotypic spectrum ranging from classical autosomal-recessive Wolfram syndrome to autosomal-dominant Wolfram‑like disorders. Dominant variants may disrupt endoplasmic reticulum (ER) homeostasis, calcium handling, and ER-mitochondria communication. Here, we report a Slovak male patient with a complex multisystem Wolfram‑like phenotype and identify a rare heterozygous in‑frame deletion in WFS1 (c.2608_2619del, p.870_873del). We aimed to determine its pathogenic potential through structural modelling and functional assays. Methods The genetic aetiology was investigated by Sanger sequencing, WGS and MLPA. Structural consequences of the deletion were analysed using AlphaFold3 modelling of wild‑type and mutant wolframin, followed by hydrogen‑bond quantification in ChimeraX. Functional studies were performed in HeLa cells expressing wild‑type WFS1, the rare p.870_873del variant, and two pathogenic controls (p.E809K, p.P724L). ER morphology was assessed by confocal microscopy. ER stress activation was quantified using ERSE‑luciferase reporter assays, XBP1 splicing analysis, and qPCR of UPR‑related genes. Mitochondrial fusion dynamics were measured using the photoconvertible mito‑KikGR1 system. Results The patient presented with early‑onset insulin‑dependent diabetes mellitus, bilateral cataracts, sensorineural hearing loss, autism spectrum disorder, paroxysmal events, and additional systemic comorbidities. Genetic analysis identified a de novo in‑frame deletion affecting four amino acid residues. Structural modelling showed that the deleted region contributes to a C‑terminal hydrogen‑bonding network, and its loss resulted in a significant reduction of stabilizing interactions. Although ER morphology remained preserved, cells expressing the p.870_873del variant displayed markedly reduced mitochondrial fusion, comparable to both pathogenic controls, indicating impaired ER–mitochondria crosstalk. Functional assays further demonstrated pronounced ER stress, evidenced by significantly increased ERSE‑luciferase activity, increased XBP1 splicing, upregulation of DDIT3 (CHOP), and mild induction of HSPA5 (BiP), consistent with activation of the unfolded protein response. Conclusions We identified a rare likely pathogenic p.870_873del WFS1 variant associated with an autosomal-dominant WFS1‑related disorder and a multisystem Wolfram‑like phenotype. Combined structural and functional evidence indicates that this variant disrupts protein stability, activates ER stress, and impairs ER–mitochondria communication, supporting its potential pathogenic role.